2018
DOI: 10.1007/s11548-018-1713-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical skills: Can learning curves be computed from recordings of surgical activities?

Abstract: Preliminary results suggest that our approach constitutes a useful addition to surgical training monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…They also showed how their proposed approach [33] allows the use of both kinematic and video data. However, studies in [34,18,35] showed that feedback on medical practice allows surgeons to improve their performance and achieve even higher skill levels. Hence the main drawback of the previous approaches is the difficulty for the trainees to understand the output and to use it as a feedback to improve their performance.…”
Section: Related Workmentioning
confidence: 99%
“…They also showed how their proposed approach [33] allows the use of both kinematic and video data. However, studies in [34,18,35] showed that feedback on medical practice allows surgeons to improve their performance and achieve even higher skill levels. Hence the main drawback of the previous approaches is the difficulty for the trainees to understand the output and to use it as a feedback to improve their performance.…”
Section: Related Workmentioning
confidence: 99%
“…Research on motor sequence 11 13 , implicit 14 , 15 , and statistical learning 16 has provided evidence of underlying neural and cognitive mechanisms, but has generally been limited to highly artificial tasks such as executing invariant key-press sequences or recognizing simple artificial grammars of known structure. This limits our ability to generalize findings to understand the learning and execution of the real-world skills 17 , 18 of interest to fields ranging from sport science 19 and surgery 20 , to human behavioral ecology 21 , and comparative psychology 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Research on motor sequence [11][12][13] , implicit 14,15 , and statistical learning 16 has provided evidence of underlying neural and cognitive mechanisms, but has generally been limited to highly artificial tasks such as executing invariant key-press sequences or recognizing simple artificial grammars of known structure. This limits our ability to generalize findings to understand the learning and execution of the real-world skills 17,18 of interest to fields ranging from sport science 19 and surgery 20 , to human behavioral ecology 21 , and comparative psychology 22 .…”
Section: Introductionmentioning
confidence: 99%